THE CATEGORY OF BEAUTY AS A POWERFUL INSTRUMENT OF “MASS CULTURE” IN THE ERA OF GLOBALIZATION - Mirakbarova Dildora Miralisher qizi (Web of Journals Publishing, 2026)
In the era of globalization, many fields, including aesthetics within philosophy, have undergone significant changes. Centuries-old standards of inner and outer beauty have been replaced by false, artificial standards that have negatively impacted people's aesthetic tastes. This article conducts a comparative study of the secular and religious foundations of beauty, and analyzes it as one of the weapons of “mass culture”.
Keywords: Ethics, aesthetics, beauty, beauty standards, “mass culture”, falsehood, outer and inner beauty.